On Symmetric Higher (U, R)-n-Derivation of Prime Rings - Khaleel Faraj, Anwar; Hadi, Marwa (Al-Qadisiyah Journal of Pure Science, 2020)
The main aim of this paper is to deﬁne the notions of Symmetric higher (U,R)-n-derivation, (U,R) n-derivation, Jordan(U,R)-n-derivation and higher n-derivation of prime ring to generalize Awtar’s theorem of derivation on Lie ideal of prime ring to symmetric higher(U,R)-n-derivation.